SALAM DAN UNGKAPAN PERPISAHAN DALAM BAHASA INGGRIS DAN BAHASA SANGIHE (SUATU ANALISIS KONTRASTIF) - SRIJONO, AMELIA PRATIWI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â ThisÂ  title of this research is â€œSalam dan Ungkapan Perpisahan dalam Bahasa Inggris dan Bahasa Sangihe : Suatu Analisis Kontrastifâ€. The aims of this study are to identify, describe and contrast the forms and pattern of greetings and leave-takings in English and Sangiric Language. Â This research uses descriptive and contrastive analysis. The data in English were collected from books related to sociolinguistics, book of speaking, and source from internet, the data in Sangiric LanguageÂ  were collected by writing and recording the conversations that occurred on the situation, the time and opportunity in places such as: the conversation that occurred while passing on the street, conversations between family members (in the house), a conversation between teachers and school officials, a conversation at the office, place of worship and other, the data Analyzed were using the consepts of Fishman, Tillit and Bruder. Â The result of this research shows that greetings and leave-takings in English and Sangiric Language have two forms; they are formal and informal. In addition, the writer finds that there are three patterns in English and Sangiric Language on greetings. Those patterns are theÂ  mutual formal greetings, the mutual informal greetings and the non mutual greetings. The patterns of English leave-taking are the same as their greetings. On the other hand, Sangirics Language has only two patterns of non mutual leave-takings, formal and informal. Â Greetings and leave-takings in English and Sangiric Language has differences. For instance, greetings and leave-takings in English are various. Meanwhile in Sangiric language are limited. Â Keywords : Greetings and leave-takings English, Sangiric Language, ContrastiveÂ  Analysis.